Income and Expenses of The Organization: Analysis and Optimization (on the Example of the Organization LLC "UZSI") ("Journal "U". Economy. Management. Finance.", 2021)
The scientific article is devoted to the analysis of income and expenses of the organization of LLC "UZSI" and the development of measures aimed at their optimization. The relevance of the study is due to the need to develop mechanisms aimed at increasing the profitability of the business of organizations by reducing the size of costs and expenses in production activities. Within the framework of the article, the goals for which the analysis and optimization of the income and expenses of the organization are analyzed are considered. The dynamics of income and expenses of the enterprise LLC "UZSI" is analyzed. The directions of their optimization in order to increase the net profit are considered.
Keywords: income optimization; cost optimization; analysis of income; cost analysis; profit of the enterprise